Estimating Environmental Hazard and Risks from Exposure to Per‐ and Polyfluoroalkyl Substances (PFASs): Outcome of a SETAC Focused Topic Meeting. (1st July 2020) - Johnson, Mark S.; Buck, Robert C.; Cousins, Ian T.; Weis, Christopher P.; Fenton, Suzanne E.
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are a group of highly fluorinated synthetic chemicals that were originally developed for uses as surfactants and surface protectors. Increasingly, specific substances of this class are being found in environmental media (e.g., surface water, soils, sediments, food sources), and concerns regarding exposure to humans and environmental receptors have been described by the public, legislators, and the general population. Data suggest that some PFAS (such as certain of the long‐chain ones) bioaccumulate and have long biological half‐lives, particularly in humans. Toxicity data in various organisms are variable as are their toxicokinetics. A Society of Environmental Toxicology and Chemistry (SETAC) Focused Topic Meeting and workshop entitled Environmental Risk Assessment of PFAS convened during 12 to 15 August, 2019 in Durham, North Carolina (USA) and brought together experts from around the globe to highlight recent advances in research pertinent to evaluating environmental and human health risks from exposures. The objectives of the Focused Topic Meeting and workshop were: 1) to review new and emerging information on PFAS chemical classification and grouping, environmental chemistry, detection technology, fate and transport, exposure potential, human health toxicity, and ecological toxicity; and 2) to harness the expertise of attendees to discuss and formulate a roadmap to prioritize the study of specific PFAS with the goal of developing a risk assessment approach that considers mechanistic (including computational) data for extrapolating exposure and data across different species/scenarios and compounds within environmental exposure pathways. We present the key issues that were discussed. Environ Toxicol Chem 2021;40:543–549. © 2020 SETAC